Who Owns the Central Mosque? Ethnic Identity and the Struggle for Spiritual Space in Epe, Southwest Nigeria - Moruff Mudasiru (Yoruba Studies Review, 2021)
Religion and ethnicity are core attributes of identity in West Africa, and the majority of the population defines itself in relation to these values. But most studies of religious conflict in Nigeria focus on the conflicts between the two great world religions, Islam and Christianity. Equally, studies of ethnic conflict tend to focus on conflict between different language groups. This article shows that it is also important to focus on sub-ethnic difference, and the meso-level conflicts and tensions that often occur within each faith. In Epe, a coastal town in Lagos, southwest Nigeria over eighty percent of the population profess Islam, but remain distinguished as different social and ethnic sub-groups, as “Ijebu Epe” and “Eko Epe.” Over time, both groups invested in ethno-religious contestation, which led to open conflict when they were brought together in the same local Council and differed over the ownership of the only Central Mosque in the town. The study shows that the struggle for the soul of the first Epe Central Mosque at Oke Balogun between Ijebu Epe and Eko Epe was used in pursuit of both spiritual and political power, and in order to gain control over important resources. This study therefore provides empirical evidence that ethnic and group differences do affect some aspects of religious practices and can even lead to rivalry within the same religion.